KESADARAN LINGKUNGAN TENTANG SEKOLAH ADIWIYATA - Pomarida Simbolon (Nursing Arts, 2021)
The environment for humans is a very important element in supporting life. One problem that often arises at this time is the lack of awareness of students in environmental conservation efforts so that the quality of the environment decreases. To overcome this the government established a program to increase student awareness in environmental preservation through Adiwiyata School. This study aims to determine environmental awareness about Adiwiyata School in SMP Negeri 1 Pancur Batu. This type of research is analytic descriptive with cross sectional design. The sample in this study were all students of class VIII-2 with a total sample of 30 people. Total sampling technique sampling. Data collection using questionnaire sheets. The results obtained by high environmental awareness of 20 people (66.7%). These results indicate that there is an environmental awareness of the adiwiyata school in SMP Negeri 1 Pancur Batu. It is expected that the teacher is able to increase student awareness regarding environmental preservation so that student awareness is higher. Keywords: Awareness; environment; Adiwiyata